Condrossarcoma de epiglote: relato de caso e revisão da literatura - Tagliarini, José Vicente [UNESP]; Bacchi, Carlos Eduardo [UNESP]; Yamashita, Seizo [UNESP]; Cançado, Cristiane G. (ABORL-CCF Associação Brasileira de Otorrinolaringologia e Cirurgia Cérvico-Facial, 2001)
Condrossarcoma é o sarcoma mais freqüente da laringe. Sua incidência é maior na cartilagem cricóide do que nas outras cartilagens da laringe, sendo raro que ele se origine na epiglote. Relatamos no texto um caso de condrossarcoma originado na epiglote, no qual foi realizada laringectomia subtotal com crico-hioidopexia - e realizamos revisão da literatura.

Chondrosarcoma is the most frequent sarcoma of the larynx. It is more prevalent in the cricoid and less prevalent in the other laryngeal cartilages. Chondrosarcoma is rarely located in the epiglottis. We reported a case of epiglottis chondrosarcoma that was treated with a supracricoid laryngectomy with cricohyoidopexy.
Epiglottis chondrosarcoma: review of the literature and report of one case
Keywords: condrossarcoma; laringe; laringectomia supracricóide; chondrosarcoma; larynx; supracriccoid laryngectomy